Captive Bred, Adult Giant Clams Survive Restoration in the Wild in Seychelles, Indian Ocean - Frias-Torres, Sarah (Frontiers in Marine Science, 2017)
Coral reef restoration focuses on scleractinian corals, excluding other groups that provide structural complexity to these threatened ecosystems. Giant clams share the role of ecosystem engineers alongside corals in the Indo-Pacific, but overfishing has caused widespread local extinctions. Aquaculture reduces pressure on wild populations and captive bred juveniles have been used to restore extinct populations. However, giant clam restoration has not been attempted before with adults until now. A total of 150 captive bred, adult giant clams (Tridacna maxima), 4-10 years old, shell length 99-198 mm, were relocated to a healthy reef (control site) and a restored reef (treatment site) at a coral reef restoration project in Seychelles, Indian Ocean, in two sequential experiments. The first experiment started in April (calm season, NW Monsoon), deployed 30 clams, 15 per site at 12 m depth, and lasted 20 weeks. The second experiment started in June (rough season, SE Monsoon), deployed 120 clams, 60 per site at 6 m and 12 m depth, and lasted 11 weeks. T. maxima were measured and double tagged with glue-on shellfish tags prior to deployment. Survival was monitored weekly or biweekly depending on weather conditions. Remote GoPro video cameras confirmed the transplanted T. maxima displayed normal behavior. Survival rates from Kaplan-Meier curves were 3.3 % to 66.7 %. Median survival time was 2 weeks to more than 20 weeks. T. maxima survived 2.5 to 6 times longer at the treatment site than at the control site in both experiments. T. maxima mortality was a combination of transplant season, predators, byssal re-attachment and wave swells. In the first experiment, mortality was due to octopus predation and 1.8 times higher at the control site than at the treatment site. The control site was an older reef with more octopus dens resulting in higher predation. T. maxima transplanted in April had one month to re-attach before the rough season started, but those transplanted in June were mostly dislodged by wave swells. These results show captive bred, adult T. maxima survive restoration in the wild. The potential synergy of jointly restoring corals and giant clams in the Indo-Pacific region is